Gastric cancer during pregnancy: A report on 13 cases and review of the literature with focus on chemotherapy during pregnancy - Maggen, Charlotte; Lok, Christianne A; Cardonick, Elyce; van Gerwen, Mathilde; Ottevanger, Petronella B; Boere, Ingrid A; Koskas, Martin; Halaska, Michael J; Fruscio, Robert; Gziri, Mina M; Witteveen, Petronella O; Van Calsteren, Kristel; et al. (Acta obstetricia et gynecologica Scandinavica, 2020)
INTRODUCTION: Gastric cancer during pregnancy is extremely rare and data on optimal treatment and possible chemotherapeutic regimens are scarce. The aim of this study is to describe the obstetric and maternal outcome of women with gastric cancer during pregnancy and review the literature on antenatal chemotherapy for gastric cancer. MATERIAL AND METHODS: Treatment and outcome of patients registered in the International Network on Cancer, Infertility and Pregnancy database with gastric cancer diagnosed during pregnancy were analyzed. RESULTS: In total, 13 women with gastric cancer during pregnancy were registered between 2002 and 2018. Median gestational age at diagnosis was 22 weeks (range 6-30 weeks). Twelve women were diagnosed with advanced disease and died within 2 years after pregnancy, most within 6 months. In total, eight out of 10 live births ended in a preterm delivery because of preeclampsia, maternal deterioration, or therapy planning. Two out of six women who initiated chemotherapy during pregnancy delivered at term. Two neonates prenatally exposed to chemotherapy were growth restricted and one of them developed a systemic infection with brain abscess after preterm delivery for preeclampsia 2 weeks after chemotherapy. No malformations were reported. CONCLUSIONS: The prognosis of gastric cancer during pregnancy is poor, mainly due to advanced disease at diagnosis, emphasizing the need for early diagnosis. Antenatal chemotherapy can be considered to reach fetal maturity, taking possible complications such as growth restriction, preterm delivery, and hematopoietic suppression at birth into account.
Keywords: Premature Birth; dospělí; preeklampsie; předčasný porod; Female; novorozenec; růstová retardace plodu; gastric cancer; Adult; ženské pohlaví; maternal outcome; lidé; Infant, Newborn; obstetric outcome; Antineoplastic Agents; Pregnancy Outcome; protinádorové látky; těhotenství; zpožděný efekt prenatální expozice; Stomach Neoplasms; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; maternofetální výměna látek; Pre-Eclampsia; nádory žaludku; Maternal-Fetal Exchange; Prenatal Exposure Delayed Effects; pregnancy; výsledek těhotenství; chemotherapy; nádorové komplikace v těhotenství; Fetal Growth Retardation; Pregnancy Complications, Neoplastic; Pregnancy; Humans